Diseño de patrones y estructuras para ser aplicadas a textiles a través de un estudio morfológico de la flora y fauna del parque turístico Nueva Loja. - Chicaiza Aguayo, Irma Fernanda (2019)
The research project focuses on visual proposals which are based on the need for the visual empowerment that Ecuador has, which has not been exploited, due to other countries trends, which have been introduced to Ecuadorian design, leaving aside their own visual diversity, despite of the fact that many designers try to recover and make the country known through visual media; the proposal in this project is: applaying Ecuadorian diversity, structures and patterns are applied to textiles using as reference the visual richness of the flora and fauna of the tourist park of Nueva Loja, with this background the main is to create patterns and structures through the morphological study of the flora and fauna of the Nueva Loja Tourist Park for its application in textiles; for this the following question is posed: How to use the flora and fauna of the Nueva Loja Tourist Park as a reference to elaborate patterns and structures through the basic design? Qualitative research will be used for: morphological analysis, interviews, photographic record, technical data sheet; while, knowing the graphic style of the patterns and structures, a focus group was carried out, which allowed to know the fashion trends in the current clothing, who are the residents who acquire garments in the micro-business Confecciones y Manualidades Carmita between the ages of 20 and 34, the methodology of Mónica Hernández (2018) will be used, which will help design the structures and patterns of flora and fauna of the place and also the technique of creation and commercialization of vector patterns by Laura Varsky ( 2018), with the use of manual to collect information and digital techniques of rapports so that once the modules are obtained, know how to convert them into patterns. The purpose of this project is to favor the clothing manufacturing micro-company of Mrs. María del Carmen Aguayo, who will benefit from personalized designs on clothing fabrics and this will give an added value, because these clothing fabrics are focused on the flora and fauna of the place, with the purpose of applying it to textile products for the improvement of the microenterprise, this will cause an appreciation of preservation towards the species by the representative use of these reasons, consideres as indirect beneficiaries are citizenship fron Lago Agrio, approximately 91.744 inhabitants (2015), who will be the ones who will buy the clothing fabrics for their use; In addition, this project may give way to a labor enterprise in terms of textile clothing and increase job growth.